2010
DOI: 10.1159/000302738
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Genetic Variant in the <i>ALOX5AP</i> with Higher Risk of Ischemic Stroke: A Case-Control, Meta-Analysis and Functional Study

Abstract: Background: Variants in the 5-lipoxygenase-activating protein (ALOX5AP) and phosphodiesterase 4D (PDE4D) genes have first been associated with ischemic stroke (IS) through whole-genome linkage screens. However, association studies obtained conflicting results. We aimed to investigate the contribution of selected single nucleotide polymorphisms (SNPs) in these genes for the first time in a large Iberian population. Methods: A case-control design was used to analyze one SNP in ALOX5AP and five SNPs in PDE4D in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][24][25][26] The meta-analysis thus involved a total of 20 populations from 17 publications when our current study was included.…”
Section: Meta-analysismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][24][25][26] The meta-analysis thus involved a total of 20 populations from 17 publications when our current study was included.…”
Section: Meta-analysismentioning
confidence: 99%
“…No variants in the coding sequence of the ALOX5AP gene that lead to amino acid substitution have been found [24]. Domingues-Montanari et al [20] found that SG13S114 SNP genotypes modulate the mRNA level of the ALOX5AP gene and that mRNA levels were higher in ischemic stroke cases than in controls. Helgadottir et al [7] found that LTB 4 generation by neutrophils stimulated with ionomycin was greater in individuals with myocardial infarction than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Another SNPs-based ALOX5AP haplotype (Hap B) showed a significant association with MI in a British cohort [7]. Replications of these findings have been conducted in various populations [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] and the results are controversial [24]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 2 ethnic specific metaanalyses were published. Domingues-Monatanari et al [18] (2010) reported that none of the SNPs in the PDE4D gene was associated with ischemic stroke in the Iberian population. However, Xu et al [19] (2010) found an association between SNP83 and ischemic cerebral infarction in Asian populations.…”
mentioning
confidence: 99%